African Sustainable Development Report 2020 - United Nations Economic Commission for Africa (United Nations, 2022)
The 2020 African Sustainable Development Report is the fourth in a series of reports dating back to 2017. These reports have sought to assess the progress and ongoing challenges faced by African States in meeting the Sustainable Development Goals (SDGs) included in the United Nations 2030 Agenda for Sustainable Development and the corresponding goals of the African Union provided in Agenda 2063. This year’s report uses an analytical lens that places all the SDGs into five “Pillars” or clusters: People, Prosperity, Planet, Peace, and Partnerships. These five Pillars break down the goals and targets into smaller areas of analysis and focus on higher-level development objectives without losing sight of the overall trajectory of the goals and targets. The objective of the analysis is therefore to carry out a holistic examination of each of the Pillars, rather than examine each of the goals that fall within each Pillar. To further focus the Report, wherever possible, the analysis focuses on comparing the progress and challenges according to Africa’s five commonly defined sub regions: Northern Africa, Western Africa, Central Africa, Eastern Africa, and Southern Africa.